Factors regarding the spatial variability of soil organic carbon in a Mexican small watershed - Aguirre-Salado, Olimpya; Pérez-Nieto, Joel; Aguirre-Salado, Carlos; Monterroso-Rivas, Alejandro (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
Understanding the stocks of Soil Organic Carbon (SOC) and elucidating the variables influencing its spatial distribution within a small watershed are imperative for advancing targeted climate change mitigation strategies, specifically directed toward soil and water conservation. The selection of this watershed is predicated upon its three-decade-long implementation of diverse soil and water conservation practices. Therefore, the objective of this study was to analyze land use, vegetation cover, slope and soil and water conservation practices (SCWP) as factors that influence the variability and spatial distribution of soil organic carbon in a small basin in the Mixteca Alta region of the state of Oaxaca. Mexico. Soil samples (77) were collected to determine SOC storage. These samples were interpolated using the QGIS Smart-Map plugin to obtain a spatial COS predictive model. Thematic maps were generated for each factor. Areal statistics, Pearson’s correlation and principal component analysis (PCA) were performed to explain COS variability. The results in the variability of SOC with respect to vegetation cover and land use, showed adult pine plantations with the highest value of SOC with 36.8 t.ha-1, followed by seasonal agriculture with 28.8 t.ha-1. The most effective management practice for storing COS was the stone terrace with 35.0 t.ha-1. Our results indicate that vegetation cover and land use complemented by soil and water conservation practices are the main drivers of SOC storage in small watersheds.